Под знаменем революции: [воспоминания 1864-1890 гг.] / Феликс Кон - Кон Феликс Яковлевич (Детгиз, 1935)
Экземпляры: КХ (20101207) / Инвентарный номер: д1708 / Цена: 3.45 / Сис.шифр: 66.61(2)8 / Авт.знак: К 64 / ГРНТИ: 11 / ББК: 66.69(2)КПСС,8